Impact of Treatment Delay in Head and Neck Mucosal Melanoma on Overall Patient Survival - Martin, Elaine C.; Abiri, Arash; Tsutsumi, Kotaro; Goshtasbi, Khodayar; Torabi, Sina J.; Kuan, Edward C. (Journal of Neurological Surgery Part B: Skull Base, 2023)
Objectives Head and neck mucosal melanoma (HNMM) is a rare malignancy with high mortality. This study evaluates the impact of treatment delays on overall survival in HNMM.Design/Setting/Participants A retrospective review of patients with surgically managed HNMM treated with adjuvant radiation was performed from the 2004–2016 National Cancer Database.Main Outcome Measures Durations of diagnosis-to-treatment initiation (DTI), surgery-to-radiotherapy initiation (SRT), duration of radiotherapy (RTD), surgery-to-immunotherapy initiation (SIT), diagnosis-to-treatment end (DTE), and total treatment package (TTP) were calculated.Results A total of 1,011 patients (50.7% female, 90.5% Caucasian) met inclusion criteria. Median DTI, SRT, RTD, SIT, DTE, and TTP were 30, 49, 41, 102, 119, and 87 days, respectively. Only longer DTE was associated with decreased mortality (hazard ratio, 0.720; 95% confidence interval, 0.536–0.965; p = 0.028).Conclusion DTI, SRT, RTD, SIT, and TTP do not significantly affect overall survival in patients with HNMM who undergo surgery and adjuvant radiation. Longer DTE is associated with improved survival in this population.Level of Evidence 4.
Keywords: mucosal melanoma; treatment delay; survival; head and neck cancer; sinonasal cancer